Top predators constrain mesopredator distributions - Thomas M. Newsome (Nature Portfolio, 2017)
Top predators can reduce local mesopredator abundance either through direct predation or behavioural changes. Here, Newsome and colleagues demonstrate at a landscape scale across three continents that mesopredator populations are suppressed at the core, but less so on the periphery, of top predators’ ranges.